Evaluation Scale of Sepsis II severity score - Syplyviy, V. A.; Grinchenko, S. V.; Ievtushenko, D. V.; Ievtushenko, A. V. (Modern medical technology, 2019)
Background. Actually sepsis is one of the main causes of high lethality among surgical patients. The purpose of this study. Is improvement of Sepsis severity evaluation Score based on available clinical and laboratory indicators. Materials and methods. 140 patients with surgical sepsis and purulent focuses localized in skin and subcutaneous tissue, abdominal cavity, lung, urogenital system were included to investigation. Results. Improved Sepsis severity evaluation Score includes clinical characteristics (estimation of consciousness, systolic blood pressure, heart rate, respiratory rate, daily diuresis, body temperature), blood system`s reaction, indicators of acute physiological disorders of kidneys and liver. Evaluation score includes localization of purulent focus, pathogen type, patient`s age, accompanied chronic pathology. Conclusions. Use of Improved Sepsis severity evaluation Score, based on available clinical and laboratory indicators, allows to estimate severity and unfavorable outcome risk in patients with having sepsis with reasonable accuracy.